PERANCANGAN AULA DAN FASILITAS PEDESTRIAN DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 PADANG - Hendra Dona Putra; Drs. Revian Body, MSA (CIVED, 2019)
Abstract —The background of this design is the lack of school infrastructure in SMKN 1 Padang, including pedestrian facility for linking all buildings and assembly hall as a meeting room for school stakeholder. The design scheme includes programming, data analysis, concept making, and design activities. Primary data were obtained from interviews and field surveys, while secondary data were obtained from literature study. Macro analysis techniques were used to analyze area and building site, while micro analysis was carried out toward design objects. The results of the design are 1 assemby hall and podium room with an area of 390 m2, 2 units male and female lavatory with an area of 11.5 m2 each, 2 units male and female changing room with an area of 5 m2 each, 1 unit lobby room with an area of 13.5 m2, 1 unit tool room with an area of 2.5 m2, 1 unit warehouse with an area of 2.5 m2, 1 unit reception room with an area of 4.5 m2, and pedestrian facility linking all buildings. The budget plan for the design is Rp. 3,948,434,000.00 (Three billion nine hundred forty-eight million four hundred thirty-four thousand rupiahs). Keywords: Assembly Hall Design, Pedestrian.